2013
DOI: 10.1155/2013/286534
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids Applied to Improve the Dispersion of Coagent Particles in an Elastomer

Abstract: The aim of this work was to study the activity of several ionic liquids (alkylimidazolium salts) that are used to improve the dispersion of coagent particles in peroxide-cross-linked hydrogenated acrylonitrile butadiene elastomer (HNBR). Hydrotalcite grafted with monoallyl maleate was applied as a coagent for the HNBR vulcanization. In this paper, we discuss the effect of the ionic liquids (alkylimidazolium salts) with respect to their anion (bromide, chloride, tetrafluoroborate, and hexafluorophosphate) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…In spite of the apparent dispersing properties of AMC, the mixing process during preparation of rubber compounds and resulting shear stresses could lead to the reagglomeration of CNFs in this system, as evidenced by SEM images (Figure 9A and B). In other works, it has been also observed that elastomer composites containing imidazolium ionic liquids with chloride anion exhibiting poor mechanical properties when compared with the bromides, tetrafluoroborates, and hexafluorophosphates . Le et al presented also that tetrafluoroborates considerably affect the tensile strength in contrast to the ionic liquids with chloride anion in polymer matrix filled with carbon nanotubes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the apparent dispersing properties of AMC, the mixing process during preparation of rubber compounds and resulting shear stresses could lead to the reagglomeration of CNFs in this system, as evidenced by SEM images (Figure 9A and B). In other works, it has been also observed that elastomer composites containing imidazolium ionic liquids with chloride anion exhibiting poor mechanical properties when compared with the bromides, tetrafluoroborates, and hexafluorophosphates . Le et al presented also that tetrafluoroborates considerably affect the tensile strength in contrast to the ionic liquids with chloride anion in polymer matrix filled with carbon nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…In other works, it has been also observed that elastomer composites containing imidazolium ionic liquids with chloride anion exhibiting poor mechanical properties when compared with the bromides, tetrafluoroborates, and hexafluorophosphates. 27,28 Le et al 29 presented also that tetrafluoroborates considerably affect the tensile strength in contrast to the ionic liquids with chloride anion in polymer matrix filled with carbon nanotubes. This effect has been also observed in our study.…”
Section: Mechanical Properties Of Nbr Vulcanizatesmentioning
confidence: 99%
“…This may result from the worse dispersion of the coagent particles in the elastomer matrix containing this ionic liquid and the aforementioned high-thermal and -chemical stability of BmimPF 6 . Additionally, ILs are believed to catalyze the interfacial crosslinking reactions, as reported for the peroxide crosslinking of a hydrogenated acrylonitrile–butadiene elastomer [ 16 ] and for the sulfur vulcanization of unsaturated rubbers [ 35 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to develop substances that improve the dispersion degree of coagent nanoparticles in the elastomer matrix. These potential dispersing agents can be ionic liquids (ILs) that, owing to their catalytic activity in interfacial reactions (including crosslinking reactions), can also increase the efficiency of crosslinking [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation